Observation of orbital currents in CuO. - Scagnoli, V; Staub, U; Bodenthin, Y; de Souza, R; García-Fernández, M; Garganourakis, M; Boothroyd, A; Prabhakaran, D; Lovesey, S (2011)
Orbital currents are proposed to be the order parameter of the pseudo-gap phase of cuprate high-temperature superconductors. We used resonant x-ray diffraction to observe orbital currents in a copper-oxygen plaquette, the basic building block of cuprate superconductors. The confirmation of the existence of orbital currents is an important step toward the understanding of the cuprates as well as materials lacking inversion symmetry, such as magnetically induced multiferroics. Although observed in the antiferromagnetic state of cupric oxide, we show that orbital currents can occur even in the absence of long-range magnetic moment ordering.